Experience of children attending a specialist CFS/ME service. (24th May 2012) - Beasant, L; Mills, N; Crawley, E
Abstract : Aims: Describe the experience of young people accessing a CFS/ME specialist service. Methods: In-depth qualitative interviews were conducted with 10 adolescents (age 12-18) and their mothers. Purposive sampling ensured that interviews included a range of age, sex and socio-economic status. All interviews were audio recorded and transcribed verbatim. Data was analysed using the data organisation package Nvivo, and themes were identified using techniques of constant comparison. Results: Four themes emerged from the data: A long journey to the CFS/ME Service. Parents described long and complex journeys when accessing a specialist CFS/ME service, where a lack of awareness or acceptance of their child's CFS/ME resulted in prolonged illness. "I can see the light at the end of the tunnel now, I couldn't see that 2 years ago". Gaining access – gatekeepers. Parents felt that GP's and other health care professionals acted as gate keepers preventing access to specialist services. "I think at GP level there's still either ignorance or doubt about the condition…it was only through YP34's school matron that we found out about the CFS/ME Service". Recognition and progress: - taking the next steps and treating the condition. Recognising the young person's condition and understanding the symptoms were important to at the start of treatment. "I think it's [specialist medical care] really good and it's really useful and helpful, and you know what you can do …rather than what you can't do". Opening dialogue between health care professionals and education providers. NHS clinicians talking to those in education was considered important as it helped explain prolonged absence. "They did that for me, they actually wrote to the school and explained, the teachers at that point hadn't been very supportive". Conclusion: Despite the publication of NICE guidance (2007) which makes clear recommendations about what children should be offered, children and their parents still experience a long and complex journey before obtaining the advice and knowledge needed to manage their illness. Recognising the illness, understanding the symptoms, and talking to other professionals are some of the key issues for families.